Spray Adjuvants with Herbicides - Peterson, Dallas E.; Kuhlman, Dennis K.; Regehr, David L. (My University, 1997)
This publication provides information on how to add spray adjuvants to pesticide spray mixtures.
MF1043_1997_08
Keywords: MF1043; Crops; Equipment and Structures; MF